Job Satisfaction of Outpatient Puskesmas and Inpatient Puskesmas Staff in Kotawaringin Barat Regency - Manurung, Togar Hasudungan; Kartasurya, Martha Irene; Sriatmi, Ayun (Interdisciplinary Social Studies, 2022)
Health staff job satisfaction impacts performance.  Puskesmas have periodically measured customer satisfaction but staff job satisfaction has never been carried out. From a preliminary study, it was found that the job satisfaction of Puskesmas  staff in Kotawaringin Barat Regency was still low. To find out the difference in job satisfaction of inpatient Puskesmas staff with outpatient health centers. Design cross-sectional research  with quantitative approach. The research population of inpatient and outpatient health center staff in Kotawaringin Barat District. Recruitment of subjects is carried out through Puskesmas. From 14 outpatient health centers, 3 Puskesmas were selected and from 4 inpatient health centers, 2 Puskesmas were selected. A total of 40 subjects filled out the questionnaire which was distributed electronically. Data analysis was carried out with an independent t test to distinguish job satisfaction. High job satisfaction at outpatient health centers is on the supervision factor, and policies are 62%, motivation is 57%, respectively, while low satisfaction in the physical work environment is 19%, on occupational safety and security factors, incentives, capitation services are 33% each, and work culture is 38%. High job satisfaction at inpatient health centers in the form of work culture factors, and capitation services were 68%, respectively, work results were 63%, and 58% each in the factors of co-workers, occupational security and safety, opportunities to improve skills and skills, while low satisfaction in the physical work environment was 16%, incentives were 16%, workload was 37%, supervision was 42%, and policies were 42%. There is no significant differencebetween  work complacencyin outpatient health centers and inpatient high school health centers (p=0.317).